The Mizrahi era of rebellion : Israel's forgotten civil rights struggle, 1948-1966 - Roby, Bryan K. (Contemporary issues in the Middle East., 2015)
During the postwar period of 1948-56, over 400,000 Jews from the Middle East and Asia immigrated to the newly established state of Israel. By the end of the 1950s, Mizrahim, also known as Oriental Jewry, represented the ethnic majority of the Israeli Jewish population. Despite their large numbers, Mizrahim were considered outsiders because of their non-European origins. Viewed as foreigners who came from culturally backward and distant lands, they suffered decades of socioeconomic, political, and educational injustices. In this pioneering work, Roby traces the Mizrahi population's struggle for equality and civil rights in Israel. Although the daily "bread and work" demonstrations are considered the first political expression of the Mizrahim, Roby demonstrates the myriad ways in which they agitated for change. Drawing upon a wealth of archival sources, many only recently declassified, Roby details the activities of the highly ideological and politicized young Israel. Police reports, court transcripts, and protester accounts document a diverse range of resistance tactics, including sit-ins, tent protests, and hunger strikes. Roby shows how the Mizrahi intellectuals and activists in the 1960s began to take note of the American civil rights movement, gaining inspiration from its development and drawing parallels between their experience and that of other marginalized ethnic groups. The Mizrahi Era of Rebellion shines a light on a largely forgotten part of Israeli social history, one that profoundly shaped the way Jews from African and Asian countries engaged with the newly founded state of Israel. --Amazon